QUANTIFICATION OF THROMBUS BURDEN AND IDENTIFICATION OF ITS DETERMINANTS IN PATIENTS OF ST-SEGMENT ELEVATION MYOCARDIAL INFARCTION UNDERGOING PRIMARY PERCUTANEOUS INTERVENTION - KHAN , AR; AQEEL , M; AHMAD , R; HAMID , S; ARSHAD , A; ZAHOOR , S (Biological and Clinical Sciences Research Journal, 2024)
Primary PCI is the gold standard treatment of STEMI. Thrombus Burden in coronary vessels is the main challenge for a good procedure prognosis. We aimed to analyze thrombus burden and to identify its determinants. Objective: To evaluate the extent of thrombus burden in coronary vessels and identify associated determinants in patients treated with primary PCI. Methods: A single center cross-sectional survey that included 470 patients was conducted at the Punjab Institute of Cardiology, Lahore from June 2023 to December 2023. We recorded demographics and risk factors in history. The angiographic findings about thrombus burden and TIMI flow were recorded before and after the procedure. All the collected data was analyzed using SPSS 23.00. Results: The mean age of the participants was 51.97±10.84 years. 410 (87.2%) were male patients and 60(12.8%) females were included in this study. 283 (60.2%) patients in our study had a high thrombus burden, whereas 187 (39.8%) patients had a low thrombus burden. There was a significant difference in TIMI flow before and after the procedure (p-value = 0.004). Four patients had no flow. All of them had high thrombus burden but were not found to be associated significantly (p-value>0.05). Conclusion: Most of the patients with STEMI had a high thrombus burden. Risk factors of IHD were not associated with high thrombus burden. 410 (87.2%) were male patients and 60(12.8%) females were included in this study.